The Challenges Hindering Effective Stakeholder Management on Construction Projects: A Case Study of the Construction of the Sesfontein Settlement Area Office - Ishitile, Eufemia (Department of Construction Economics and Management, 2023)
This study aims to understand the application of a stakeholder management strategy on construction projects and the challenges currently hindering the implementation of effective stakeholder management and how these challenges can be addressed. The qualitative research method using a single case study was used and the unit of analysis being the stakeholders involved in the planning and construction of the Sesfontein Settlement Area Office in Kunene, Namibia. Data analysis was undertaken by following a thematic approach. The results of this study indicate that failure to identify one or more stakeholders on construction projects can have an adverse effect on the project. In addition, if challenges are not considered there will be technical delays and failure on the project. The developing of strategies is the first move towards overcoming the challenges. Also, sharing of the challenges among the stakeholders is the most critical part to assist in mapping out a stakeholder management strategy for the project. The results of this research will be beneficial to the Kunene regional council and its stakeholders as it will aid in providing awareness in which stakeholders entail better emphasis with regards to stakeholder management, thereby working toward the role of implementing stakeholder management strategy on the construction project results. The study contributes to stakeholder theory, including the role of stakeholder management on construction projects. Possible research gaps and trends are presented for future research.